Analisis Faktor Fundamental dan Risiko Sistematik terhadap Harga Saham dengan Profitabilitas sebagai Variabel Intervening - Rahmat Wahyudi (Journal of Business and Economics (JBE) UPI YPTK, 2022)
This study aims to determine the effect of Earning Per Share (EPS), Current Ratio (CR), Exchange Rate and Interest Rate Risk on stock price movements with Return On Assets (EPS) as an intervening variable on property stocks listed on the Indonesia Stock Exchange 2017 -2021. The sample in this study was taken by purposive sampling method on property stocks listed on the Indonesia Stock Exchange 2017-2021. The number of samples used as many as 158 companies. The analytical method of this research is using multiple linear regression analysis method. The results of this study indicate that partially Earning per Share (EPS), has a significant effect on Return On Assets (ROA), Current Ratio (CR) has a significant effect on Return On Assets (ROA), Exchange Rates have a significant effect on Return On Assets (ROA)., Interest Rate Risk has a significant effect on Return On Assets (ROA), Earnings per Share (EPS) has a significant effect on Stock Prices, Current Ratio (CR) has a significant effect on Stock Prices, Exchange, Risk Interest has a significant effect on stock prices, Return on Assets (ROA) has a significant effect on stock prices, Earning per Share (EPS) has no significant effect on stock prices through Return On Assets (ROA) as an intervening variable, Current Ratio (CR) has no effect significant effect on stock prices through Return On Assets (ROA) as an intervening variable, exchange rate has an effect s significant no effect on stock prices through Return On Assets (ROA) as an intervening variable and Interest Rate Risk has no significant effect on stock prices through Return On Assets (ROA) as an intervening variable on property stocks listed on the Indonesia Stock Exchange 2017-2021.